The impact of COVID-19 on trade relations between Russia and Spain: contributions from the Iberian country - A. Vallina Rodríguez; C. Camarero Bullon; T. Moreno Bueno (Ибероамериканские тетради)
It is undeniable to note that the  ties  between  countries, especially cultural,  historical,  economic   and   geopolitical,  are   rooted    in the  political foundations that have been laid  between nations and countries throughout the  process of  shaping what today is known as  international  relations,  a  discipline that  has  become  one  of the  most relevant for understanding the  contemporary world. Starting from  the  premise that human groups,  and hence the  forms  of their organization,  permanently  establish  social  links  and  interactions that constitute the   dynamic substrate  of  all  societies, it would  be appropriate to analyze how  they materialize in a specific bilateral sphere, for which a key aspect of mutual economic interests between the Russian Federation and Spain has been chosen. From an economic perspective and through the  analysis of statistics on foreign trade of goods, foreign investment and trade barriers, this research will address the  evolution of trade relations  over  the  last five  years, focusing on the  international trade situation that has occurred since the  global COVID-19 pandemic and created a multiplicity  of opportunities and challenges for trade and investment between the  two states in health sector.